AKTIVITAS ENZIM LIPASE PADA BERBAGAI KECAMBAH BIJI TUMBUHAN: A MINI REVIEW - Mita Haryani; Djihan Ryn Pratiwi; Eva Marliana (PROSIDING SEMINAR KIMIA, 2025)
Lipase is an enzyme that functions as a catalyst in the hydrolysis reaction of triglycerides into glycerol and free fatty acids. Lipase has wide applications in various fields such as the food industry, cosmetics, biotechnology, and biocatalysis. This review examines the activity of lipase enzymes derived from various tropical plant sources based on previous research results using in vitro enzymatic assay methods. Lipase activity was detected in germinated seed samples of several plant species, including Jackfruit Seed Sprouts (Artocarpus integer), Avocado Seed Sprouts (Persea americana Mill), Cocoa Seeds (Theobroma cacao L.), Indian Almond Seed Sprouts (Terminalia catappa L.), Rambutan Seed Sprouts (Nephelium lappaceum L.), Durian Seed Sprouts (Durio zibethinus R.), Kesambi Seed Sprouts (Schleichera oleosa L.), Sunflower Seeds (Helianthus annuus L.), Jatropha Seed Sprouts (Jatropha curcas L.), and Palm Princess (Veitchia merrillii). The results showed varying lipase activity values ranging from 0.100 to 41.5 U/mL, reflecting differences in expression and physiological function. The highest lipase activity was found in Kesambi Seed Sprouts (Schleichera oleosa L.) with a value of 41.5 U/mL, while the lowest was found in Cocoa Seeds (Theobroma cacao L.) with a value of 0.010 U/mL. These findings indicate that Kesambi Seed Sprouts have strong potential to be further developed as a source of lipase enzymes for various industrial and biotechnological applications. Keyword: Plants, Enzymes, Lipase, lipase enzyme activity